Discussion of 'a general framework for functional regression modelling' by Greven and Scheipl. (February 2017) - Kokoszka, Piotr; Reimherr, Matthew
Abstract: We discuss the challenge in properly assessing the uncertainty of the estimates produced by the R package pffr, especially as it pertains to constructing confidence bands and computing p-values in functional linear models. We also present an approach that partially addresses some of these issues. Simulations are provided to help articulate these ideas.